Fault identification in nonlinear hybrid systems. (February 2021) - Zhirabok, Alexey; Zuev, Alexander; Filaretov, Vladimir; Shumsky, Alexey
Abstract: The problem of fault identification in hybrid systems is investigated. It is assumed that the hybrid systems under consideration consist of a finite automaton, the set of nonlinear differential equations, and so-called mode activator that coordinates the action of these two parts. To solve the fault identification problem, sliding mode observers are used. The suggested approach for constructing sliding mode observers is based on the reduced order model of the original system. This allows to reduce complexity of sliding mode observers and relax the limitations imposed on the original system. Examples illustrate details of the solution. Highlights: To construct SMO, we use reduced order model insensitive to the disturbance. This allows to relax the limitations imposed on the original system. Next, the use of reduced order model allows to reduce complexity of SMO. When the FA part of HS is unobservable, it imposes restrictions on the dynamic part. We study these restrictions, the main purpose is to find solvability conditions.